2018
DOI: 10.1101/323048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel LC system embeds analytes in pre-formed gradients for rapid, ultra-robust proteomics

Abstract: To further integrate mass spectrometry (MS)-based proteomics into biomedical research and especially into clinical settings, high throughput and robustness are essential requirements. They are largely met in high-flow rate chromatographic systems for small molecules but these are not sufficiently sensitive for proteomics applications. Here we describe a new concept that delivers on these requirements while maintaining the sensitivity of current nano-flow LC systems. Low-pressure pumps elute the sample from a d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The desalted peptides were dissolved in 50 µl of solvent-A (0.1% formic acid in water) prior to loading on to Evotips (https://www.evosep.com/) as described in [62]. Briefly, the Evotips are activated by incubating in 100% isopropanol and then washed twice with 20 µl of Solvent-B (100% Acetonitrile in 0.1% formic acid by volume) and subsequently equilibrated by washing twice with 20 µl of solvent-A (0.1% formic acid in water).…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…The desalted peptides were dissolved in 50 µl of solvent-A (0.1% formic acid in water) prior to loading on to Evotips (https://www.evosep.com/) as described in [62]. Briefly, the Evotips are activated by incubating in 100% isopropanol and then washed twice with 20 µl of Solvent-B (100% Acetonitrile in 0.1% formic acid by volume) and subsequently equilibrated by washing twice with 20 µl of solvent-A (0.1% formic acid in water).…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…Technological advancements in instrumentation, coupling to mass spectrometer and improvements in separation performance have accompanied this development [4,27]. Even though nanoLC-MS is still the most commonly used analysis platform for advanced proteomics [28,29], several studies have demonstrated that combination of nanoLC-MS and CE-MS methods increase the number of identified proteins as they are orthogonal and provide complementary results [30].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these approaches fail to achieve the meaningful depth of quantitative proteome coverage within short experimental times. Many of the recent efforts were focused on hybrid experimental pipelines, in which MS/MS-based identification is combined with MS1-based quantitation 3,16 .…”
mentioning
confidence: 99%